2020
DOI: 10.1101/2020.05.23.20111104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lifestyle acquired immunity, decentralized intelligent infrastructures and revised healthcare expenditures may limit pandemic catastrophe: a lesson from COVID-19

Abstract: Human race has often faced pandemic with substantial number of fatalities. As COVID-19 pandemic reached and endured in every corner on earth, countries with moderate to strong healthcare support and expenditure seemed to struggle in containing disease transmission and casualties. COVID-19 affected countries have variability in demographic, socioeconomic and life style health indicators. At this context it is important to find out at what extent these parametric variations are actually modulating disease outcom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 71 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…In addition, sufficient testing is required to properly declare COVID-19 related deaths and recovery. In our previous report (May 26, 2020), analyzing 91 countries’ number of tests performed per 100 K population data we found positive as well as negative correlation with positive cases and test positive (%) respectively with statistical significance [12]. Countries where limited numbers of tests were performed test positive (%) was comparatively higher.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, sufficient testing is required to properly declare COVID-19 related deaths and recovery. In our previous report (May 26, 2020), analyzing 91 countries’ number of tests performed per 100 K population data we found positive as well as negative correlation with positive cases and test positive (%) respectively with statistical significance [12]. Countries where limited numbers of tests were performed test positive (%) was comparatively higher.…”
Section: Discussionmentioning
confidence: 78%
“…In our previous report we also found that countries with high median age showed strong association with COVID-19 case fatality rate [12]. This was mainly due to prevalence of non communicable diseases as contributing factor for comorbidity and reduced immunity of elderly people.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Ahmed et al (2020) focus on different demographic, socioeconomic, and lifestyle health factors in countries to explain the variety of COVID-19 effects in society. This study by Ahmed et al (2020) suggests that health expenditure per capita has a positive relation with case recovery; in particular, countries having high healthcare investments associated with high average age and proportion of urban population have high number of case fatality; as a consequence, investment in health sector is one of the factors that plays a vital role to control the spread of COVID-19 pandemic. Barrera-Algarín et al (2020) state that in Europe lower investment in health per capita is associated with high numbers of COVID-19 deaths per million inhabitants; in general, a high negative impact of COVID-19 in terms of mortality is due to low expenditure in public health associated with high socioeconomic inequality.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Kapitsinis (2020) investigates the diffusion of the novel coronavirus in nine European countries and pinpoints that health investments play a vital role to alleviate mortality rate of COVID-19. Ahmed et al (2020) focus on different demographic, socioeconomic, and lifestyle health factors in countries to explain the variety of COVID-19 effects in society. This study by Ahmed et al (2020) suggests that health expenditure per capita has a positive relation with case recovery; in particular, countries having high healthcare investments associated with high average age and proportion of urban population have high number of case fatality; as a consequence, investment in health sector is one of the factors that plays a vital role to control the spread of COVID-19 pandemic.…”
Section: Theoretical Frameworkmentioning
confidence: 99%